Common perinatal mental disorders in northern Viet Nam: community prevalence and health care use - Jane Fisher; Thach Tran; Buoi thi La; Kelsi Kriitmaa; Doreen Rosenthal; Tuan Tran (Bulletin of the World Health Organization, 2010)
OBJECTIVE: To establish the prevalence of common perinatal mental disorders their determinants, and their association with preventive health care use among women in one rural and one urban province in northern Viet Nam. METHODS: We conducted a cross-sectional survey of cohorts of pregnant women and mothers of infants recruited systematically in 10 randomly-selected communes. The women participated in psychiatrist-administered structured clinical interviews and separate structured interviews to assess sociodemographic factors, reproductive health, the intimate partner relationship, family violence and the use of preventive and psychiatric health care. Associations between these variables and perinatal mental disorders were explored through univariate analyses and multivariable logistic regression. FINDINGS: Among women eligible for the study (392), 364 (93%) were recruited. Of these, 29.9% (95% confidence interval, CI: 25.20-34.70) were diagnosed with a common perinatal mental disorder (CPMD). The frequency of such disorders during pregnancy and in the postpartum period was the same. Their prevalence was higher among women in rural provinces (odds ratio, OR: 2.17; 95% CI: 1.19-3.93); exposed to intimate partner violence (OR: 2.11; 95% CI: 1.12-3.96); fearful of other family members (OR: 3.36; 95% CI: 1.05-10.71) or exposed to coincidental life adversity (OR: 4.40; 95% CI: 2.44-7.93). Fewer women with a CPMD used iron supplements than women without a CPMD, but the results were not statistically significant (P = 0.05). None of the women studied had ever received mental health care. CONCLUSION: Perinatal depression and anxiety are prevalent in women in northern Viet Nam. These conditions are predominantly determined by social factors, including rural residence, poverty and exposure to family violence. At present the needs of women with common perinatal mental disorders are unrecognized and not attended to and their participation in essential antenatal preventive care appears to be compromised.